Silicon charge detector for the CREAM experiment - S. Coutu; H. S. Ahn; M. H. Lee; S.J. Baek; Eun-Suk Seo; Riccardo Zei; S. Minnick; R. Sina; J. A. Jeon; J. J. Beatty; J.H. Park; J. T. Childers; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2007)
Abstract The Cosmic Ray Energetics And Mass (CREAM) payload had its first successful flight in December 2004 from McMurdo Station, Antarctica as a Long Duration Balloon mission. Its aim is to explore the supernova acceleration limit of cosmic rays, the relativistic gas of protons, electrons and heavy nuclei arriving at Earth from outside of the solar system. The instrument is equipped with several systems to measure charge and energy spectra for Z = 1 – 26 nuclei over the energy range 10 11 – 10 15 eV . The Silicon Charge Detector (SCD) is a precision device to measure the charge of incident cosmic rays. The design, construction, integration and preliminary performance of the SCD are detailed in this paper.